Emergence and adaptive evolution of Nipah virus. Issue 1 (10th September 2019) - Li, Kemang; Yan, Shiyu; Wang, Ningning; He, Wanting; Guan, Haifei; He, Chengxi; Wang, Zhixue; Lu, Meng; He, Wei; Ye, Rui; Veit, Michael; Su, Shuo
Abstract: Since its first emergence in 1998 in Malaysia, Nipah virus (NiV) has become a great threat to domestic animals and humans. Sporadic outbreaks associated with human‐to‐human transmission caused hundreds of human fatalities. Here, we collected all available NiV sequences and combined phylogenetics, molecular selection, structural biology and receptor analysis to study the emergence and adaptive evolution of NiV. NiV can be divided into two main lineages including the Bangladesh and Malaysia lineages. We formly confirmed a significant association with geography which is probably the result of long‐term evolution of NiV in local bat population. The two NiV lineages differ in many amino acids; one change in the fusion protein might be involved in its activation via binding to the G protein. We also identified adaptive and positively selected sites in many viral proteins. In the receptor‐binding G protein, we found that sites 384, 386 and especially 498 of G protein might modulate receptor‐binding affinity and thus contribute to the host jump from bats to humans via the adaption to bind the human ephrin‐B2 receptor. We also found that site 1645 in the connector domain of L was positive selected and involved in adaptive evolution; this site might add methyl groups to the cap structure present at the 5′‐end of the RNA and thus modulate its activity. This study provides insight to assist the design of early detection methods for NiV to assess its epidemic potential in humans.